The long song [videorecording (DVD)] - Lawrance, Tamara, 1994-; Atwell, Hayley, 1982-; Lowden, Jack, 1990-; Levy, Andrea, 1956-2019 (PBS, 2021)
Set during the final days of slavery in 19th century Jamaica, following the trials, tribulations and survival of July and her odious mistress Caroline on a sugar plantation.